A critical analysis of diet in seventeen deep sea fishes along the South-eastern Arabian Sea - Viji, V.; Harish, K. C.; Korath, Alphi; Sileesh, M.S (Indian Journal of Fisheries, 2017)
Diet analysis of 1190 fishes belonging to 17 species of deep sea fishes were conducted. The samples were collected from the South-eastern Arabian Sea in bottom trawl by the research vessel FORV Sagar Sampada (cruise no. 322 and 345) during January 2014 and October 2015, between lat. 7- 150N and long. 78 - 720E in the depth range 200 - 1000 m. Diet composition, feeding strength, size range, depth range, distribution and index of preponderance were ascertained for all the species. It was observed that the deep sea fishes mainly feed on benthic and epibenthic organisms such as fishes, shrimps, crabs and squids, revealing their carnivorous nature. Deep sea shrimps are one of the major diet components of these fishes, which is an indication of the availability of good quantity of deep sea shrimps, along the South-eastern Arabian Sea and this abundant population can be commercially utilised in order to lessen the pressure of overexploitation being experienced in case of coastal shrimps.